Análise multibloco em bolos preparados com farinhas alternativas ao trigo - Cabral, Nayara Araujo (2024)
Some foods such as fruits, vegetables, seeds and grains have a high concentration of antioxidants, a property that is responsible for combating free radicals. Free radicals, when in excess in our body, can be harmful, as they are unstable and reactive molecules released by the human body that can cause aging and cell death. Oxidative stress is the stage in which antioxidant levels in the body are not sufficient to neutralize the harmful effect of free radicals that are present. Wheat flour is essential for the preparation of various foods such as breads and cakes, but this food is not the most recommended when aiming for weight loss or nutritional diversification, as wheat loses a good part of its nutrients when processed. Furthermore, replacing it with other flours can be of great value for people who are intolerant or allergic to gluten. As a response to this problem, there are several alternative flours to wheat, with different and positive nutritional properties depending on the raw material. Some flours, such as orange peel, may even have byproducts as their raw material. This study aimed to prepare gluten-free cakes prepared using ten different alternative flours to wheat and characterize texture and color parameters, as well as the analysis of antioxidants. The data were subjected to univariate analysis using the Tukey test. The ComDim method was used for multiblock data analysis in order to verify the differences and similarities between the samples considering all data tables simultaneously. The first two dimensions (CD1 and CD2) accumulated 96.5% of the total data variance. Most of the variance related to antioxidant results is in CD1, while the variance in color and texture data is mainly represented in CD1 and CD2. The increase in antioxidant activity stood out in samples of lemon, broccoli, orange peel and Brazil nuts. It was observed that the chewiness and gumminess texture parameters were essential for differentiating the samples. The samples with results most similar to the control sample (wheat flour) were those of chickpeas, peas and buckwheat.